1992
DOI: 10.1007/bf02067003
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial analysis of septic bile and septic complications in biliary surgery

Abstract: A unifactorial analysis for possible risk factors was applied to 2,700 consecutive operations for benign disease of the biliary tract. A series of high risk factors in relation to positive bacteriology and septic complication could be identified. These risk factors were patients who were elderly (greater than 70 years; p less than 0.001), those who were diabetic, those who had a serum bilirubin greater than 1.1 mg% (p less than 0.001), those who had acute cholecystitis (p less than 0.001), and those in whom ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…It has been suggested that prophylaxis be given only to patients at high risk of having bactibilia, namely patients older than 60 years, and those who present with the combination of fever, leukocytosis and hyperbilirubinemia suggesting advanced cholecystitis and/or cholangitis. [13][14][15] There is no evidence, however, to justify prolonging antibiotic therapy for patients with an uncomplicated course, or to administer oral antibiotics upon hospital discharge in such patients. 16 This practice unnecessarily prolongs hospital stay and increases the cost of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that prophylaxis be given only to patients at high risk of having bactibilia, namely patients older than 60 years, and those who present with the combination of fever, leukocytosis and hyperbilirubinemia suggesting advanced cholecystitis and/or cholangitis. [13][14][15] There is no evidence, however, to justify prolonging antibiotic therapy for patients with an uncomplicated course, or to administer oral antibiotics upon hospital discharge in such patients. 16 This practice unnecessarily prolongs hospital stay and increases the cost of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…14 The risk factors for bactibilia are well defined and include acute cholecystitis, common duct stones, emergency surgery, intraoperative findings and age >70 years. [15][16][17][18] It has been demonstrated that all patients found to have bactibilia at the time of cholecystectomy have at least one of these risk factors and that patients with uncomplicated gallstone disease do not show evidence of bactibilia. 6 The main aim of this study was to assess the effectiveness of a selective antibiotic prophylaxis policy limited to high risk patients undergoing LC with the development of port site infections as the primary endpoint.…”
Section: Yanni Mekhail Morris-stiffmentioning
confidence: 99%
“…Coyle et al S7 reported the results of carotid endarterectomy in 79 octogenarians at Emory University Hospital and summarized the results of five other series; morbidity and mortality were similar to those in a younger cohort ( [70][71][72][73][74][75][76][77][78][79][80][81][82][83][84] years were identical to those in 451 younger patients (Table 6.3). Although some researchers 5 0-55 ,S9,90 found increased operative mortality for pneumonectomy in the elderly, others 72 ,91-94 have found that the risk of major complication or death is not related to age; in addition, long-term survival is identical to that in young patients (Fig.…”
Section: Principle Iv: Emergency Surgerymentioning
confidence: 89%